Comprehensive expression analysis of Arabidopsis GA2-oxidase genes and their functional insights. (August 2019) - Li, Chen; Zheng, Lanlan; Wang, Xuening; Hu, Zhubing; Zheng, Yan; Chen, Qinhua; Hao, Xincai; Xiao, Xiao; Wang, Xuanbin; Wang, Guodong; Zhang, Yonghong
Highlights: Comprehensive expression analysis of seven GA2-oxidase genes using translational reporter lines reveals their distinct expression patterns during Arabidopsis growth and development. Overexpression of these genes inhibits high temperature-induced hypocotyl elongation. Abstract: Bioactive gibberellins (GAs) play multiple roles in plant development and stress responses. GA2-oxidases (GA2oxs) are a class of 2-oxoglutarate-dependent dioxygenases that regulate the deactivation of bioactive GAs. In this study, we investigated the phylogeny and domain structures of the seven GA2ox genes present in the Arabidopsis thaliana genome. Comprehensive expression analysis using translational reporter lines showed that the seven GA2ox genes are differentially expressed during Arabidopsis growth and development: GA2ox1 is specifically expressed in the hypocotyl and lateral root primordium; GA2ox2 is highly expressed in aboveground tissues; GA2ox3 is expressed in the chalazal endosperm of the early embryo sac and inflorescences; GA2ox4 is expressed in the shoot apical meristem and during lateral root initiation; GA2ox6 is expressed in the maturation zone, but not in the meristem or elongating zone of the root; GA2ox7 is constitutively expressed during almost all developmental stages; and GA2ox8 is exclusively expressed in stomatal cells. Overexpression of each of these GA2ox genes inhibited high temperature-induced hypocotyl elongation in both wild-type and elongated hypocotyl 5 plants, which have an elongated hypocotyl phenotype, suggesting that these genes negatively regulate hypocotyl elongation by reducing bioactive GA levels. This study provides a valuable resource for further elucidating the roles of GA2ox genes during different stages of development.